A double-edged sword: interactions of CX3CL1/CX3CR1 and gut microbiota in systemic lupus erythematosus - Estaleen, Rana A.; Reilly, Christopher M.; Luo, Xin M. (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) is a systemic chronic disease initiated by an abnormal immune response to self and can affect multiple organs. SLE is characterized by the production of autoantibodies and the deposition of immune complexes. In regard to the clinical observations assessed by rheumatologists, several chemokines and cytokines also contribute to disease progression. One such chemokine and adhesion molecule is CX3CL1 (otherwise known as fractalkine). CX3CL1 is involved in cell trafficking and inflammation through recognition by its receptor, CX3CR1. The CX3CL1 protein consist of a chemokine domain and a mucin-like stalk that allows it to function both as a chemoattractant and adhesion molecule. In inflammation and specifically lupus, the literature displays contradictory evidence for the functions of the CX3CL1/CX3CR1 interactions. In addition, the gut microbiota has been shown to play an important role in the pathogenesis of SLE. This review highlights current studies that illustrate the interactions of the gut microbiota and CX3CR1 in SLE.